A multilingual chatbot for supporting mobile companies complaints. Case study: ATM Mobilis of Algeria. - Attaoua, Samiha; Guesmia, Chaima; Supervisor: Mehenni, Tahar (UNIVERSITY of M'SILA, 2022)
The application of artificial intelligence techniques by communication companies is changing the nature of interactions with customers. It is now possible to automate repetitive and regular work, increasing the productivity, creativity and efficiency of organizations. The customer also wants more options of independence and self-service, preferring to conduct an operation or obtain information without wasting time or ignoring it. On the other hand, in light of the competition between communication companies, each of them seeks to impose itself in the market by maintaining its customers and acquiring new customers. Therefore, an effective and profitable solution to this problem for two parties is a chatbot. It is a software application that simulates a call center employee that responds to common questions and directs customers to reduce the time spent by the user in finding the right information. In our work, we explored two different chatbot systems, the first is a Dialogflow chat bot and the second is a rules-based chat bot that supports three languages and automatically recognizes the user's language among the languages Arabic is not supported by the first type.
Keywords: Deep learning, chatbot, customer service, Dialogflow, company mobile